Thermodynamic and Kinetic Study for Corrosion of Al-Si-Cu/Y2O3 Composites - Afif Majed Anaee, Rana (Asian Journal of Chemistry, 2014)
This study involves the effect of yttria with three wt. % (1, 2 and 3 %) on the corrosion behavior of Al-Si-Cu alloy in 0.1 N NaOH solution by potentiostat at four different temperatures 303, 313, 323 and 333 K. Corrosion parameters for these composite materials were determined by Tafel extrapolation method such as corrosion potentials Ecorr, corrosion current densities icorr and Tafel slopes bc and ba. The results of electrochemical study indicates that Al-Si-Cu/1 % yttria gave the lowest corrosion rate due to behaviour of yttria as protective layer which cover the metallic surface and enhances the passive film of Al2O3, while 2 and 3 % yttria may be behave as sufficient cathode leading to increasing the corrosion of base alloy because of the inhomogenous structure of an metal matrix composite which must be considered in designing a corrosion protection system. Thermodynamic study was achieved to estimate thermodynamic quantities of corrosion process DG, DS and DH. The results show spontaneous the corrosion in 0.1 N NaOH through the negative values of Gibbs free energy for composites and the lowest spontaneous process was for Al-Si-Cu/1 % yttria, the change in entropy values were positive and the lowest value was for Al-Si-Cu/1 % yttria. Also the change in enthalpy values was positive referring to endothermic nature of corrosion process. Kinetic study was applied using Arrhenius equation to estimate activation energies and the highest activation energy was for Al-Si-Cu/1 % yttria, this means that this composite need most energy to surmount the energy barrier. The relationship existed between values of the activation energy (Ea) and logarithm of pre-exponential factor (log A) for different material suggesting the operation of a compensation effect in kinetics of corrosion. This suggests that, the corrosion reaction proceeds on surface sites, which were associated with different energies of activation.